2018
DOI: 10.1089/hum.2017.026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intrathecal Routes of Administration for Adeno-Associated Viral Vectors in Large Animals

Abstract: Delivery of adeno-associated viral (AAV) vectors into the cerebrospinal fluid (CSF) can achieve gene transfer to cells throughout the brain and spinal cord, potentially making many neurological diseases tractable gene therapy targets. Identifying the optimal route of CSF access for intrathecal AAV delivery will be a critical step in translating this approach to clinical practice. We previously demonstrated that vector injection into the cisterna magna is a safe and effective method for intrathecal AAV delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 18 publications
1
92
0
Order By: Relevance
“…A single IT injection of AAV.hGAA also led to neurologic and cardiac improvements in Pompe disease (Hordeaux et al, 2017), while similar central and peripheral benefits could be demonstrated after infusion of AAV9, AAVrh.10, and AAV.Olig001 in young Krabbe disease mice (10-11 days old; Karumuthil-Melethil et al, 2016). Overall, the transduction efficacy appears to be rather equivalent in adult mice when comparing different routes of administration in the CSF (Bey et al, 2017), but infusion of AAV9 in the cisterna magna or in the lateral ventricle has been shown to be far more potent at transducing the brain and spinal cord of cynomolgus macaques or dogs as compared with IT injection by lumbar puncture (Hinderer et al, 2018a). Whether or not placing the subject in the Trendelenburg position right after infusion can potentiate the efficacy of brain transduction by this procedure remains debated (Meyer et al, 2015).…”
Section: The Route Of Administration: a Major Variablementioning
confidence: 99%
See 1 more Smart Citation
“…A single IT injection of AAV.hGAA also led to neurologic and cardiac improvements in Pompe disease (Hordeaux et al, 2017), while similar central and peripheral benefits could be demonstrated after infusion of AAV9, AAVrh.10, and AAV.Olig001 in young Krabbe disease mice (10-11 days old; Karumuthil-Melethil et al, 2016). Overall, the transduction efficacy appears to be rather equivalent in adult mice when comparing different routes of administration in the CSF (Bey et al, 2017), but infusion of AAV9 in the cisterna magna or in the lateral ventricle has been shown to be far more potent at transducing the brain and spinal cord of cynomolgus macaques or dogs as compared with IT injection by lumbar puncture (Hinderer et al, 2018a). Whether or not placing the subject in the Trendelenburg position right after infusion can potentiate the efficacy of brain transduction by this procedure remains debated (Meyer et al, 2015).…”
Section: The Route Of Administration: a Major Variablementioning
confidence: 99%
“…Delivery to the CSF via Intracerebroventricular, Intracisternal Delivery, or Intrathecal Routes Delivery to the CSF allows for more widespread gene transfer throughout the brain and spinal cord (Hardcastle et al, 2018) while limiting systemic biodistribution ( Figure 2). However, the presence of tight junctions between ependymal cells restricts such application to certain AAV serotypes (such as AAV1, -2, -4, -5, -8, -9, rh10, and PHP.B) able to extravagate through this protective cell layer (Hinderer et al, 2018a). Importantly, the age of the animals at the time of intervention influences the transduction profile following AAV infusion in the CSF: for example, a comparative study demonstrated that intracerebroventricular (i.c.v.)…”
Section: The Route Of Administration: a Major Variablementioning
confidence: 99%
“…ICM AAV delivery offers a potential minimally invasive approach to achieve durable and widespread PGRN delivery to the CNS of GRN mutation carriers. 13,27 In the absence of an authentic animal model of FTD-GRN, we evaluated the impact of AAV-mediated PGRN expression on lysosomal abnormalities in GRN À/À mice. Recent studies revealed that PGRN is a downstream target for a lysosomal master-regulator transcription factor EB.…”
Section: Discussionmentioning
confidence: 99%
“…The delivery, intracisternally to the cisterna magna, was safe and resulted in ApoE2‐HA immunoreactivity throughout the CNS, suggesting successful targeting of AD‐associated regions. In fact, an optimized delivery protocol into the CSF of NHP was reported with translational implications for ApoE2 and other candidate targets in AD (Hinderer et al, ; Katz, Goode, Hinderer, Hordeaux, & Wilson, ). There are many other examples for potential gene therapy approaches in AD and three recent examples targeting very different pathways are outlined below: (a) The α‐secretase cleavage product of APP, APPsα, has also neurotrophic properties and has therefore been suggested for gene therapy of AD (Mockett, Richter, Abraham, & Muller, ).…”
Section: Adeno‐associated Viruses—research Tools and Gene Therapymentioning
confidence: 99%